The promoters and the barriers for organizational culture change in a Finnish construction company. Issue 4 (7th October 2019) - Teräväinen, Ville Juhani; Junnonen, Juha-Matti
Abstract : Purpose: The construction industry has struggled with efficiency issues for decades. Organizational culture is identified as one of the biggest hindrances for the enhancement of efficiency in a highly labor-intensive sector such as construction. Based on recent academic studies, Finnish construction industry professionals would embrace clan and adhocracy culture features to achieve a better level of construction efficiency. The purpose of this paper is to investigate the promoters and the barriers for making the desired culture change happen in the case company. Design/methodology/approach: The paper presents a semi-structured theme interview case study, including 12 in-depth interviews. The interviews were recorded, and later, transcribed into text, which forms the empirical data of this paper. Findings: The Finnish construction industry must adopt a holistic approach to enhance its prevailing level of efficiency through the culture change. Basic learning and knowledge management processes seem to be missing from the industry and organizational levels. Better knowledge management in the case company would be the first step to start fixing this problem. Research limitations/implications: Because of the nature of a case study, the research results can be generalized only with caution in the Finnish construction industry. Generalizing the findings in another country would require further studies in a different cultural environment, e.g. in another European country. Practical implications: The paper includes implications for the development of the organizational culture on the Finnish construction industry level and on an organizational level. Originality/value: The found influencers are discussed through Engeström's activity model for the first time in the construction culture context.